Risk perception: The social construction of spatial knowledge around climate change-related scenarios in Lima. (May 2016) - Miranda Sara, Liliana; Jameson, Shazade; Pfeffer, Karin; Baud, Isa
Abstract: Lima's environmental sustainability is threatened by increasing water scarcity, heavy rain events and limited attention for water vulnerability and climate change scenarios. In this paper we examine how knowledge construction and risk perception on water-related disaster risks and vulnerabilities affects decision-making and implementation in urban governance networks, specifically looking at some of the reasons behind high levels of risk tolerance and the lack of decision-making initiatives in putting adaptation and/or preventive measures in place. New forms of metropolitan governance have constructed spatial knowledge about water-related vulnerabilities using inclusive scenario-building processes. These unpack complexities, uncertainties and spatial inequalities in water governance, making them visible by mapping and spatial representations as strategic instrument for social and policy learning. This article analyzes two case studies, which either already are or can become disasters (scenario-building). The first, concerns the long-term plausible scenario of water scarcity and droughts analyzing population growth rates, water distribution and consumption through the Chance2Sustain research project and presenting spatial representations. The maps were used to define possible spatial intervention priorities to deal with future water vulnerabilities in Lima. The second, refers to short term extreme weather events that already manifest as mudslides and floods and El Niño in Chosica, eastern Lima. We investigate the first at the metropolitan city scale level and the second at the scale of vulnerable communities. The cases illustrate iterative spatial knowledge construction, in which processes of risk prioritization, normalization and tolerance occur, and the resulting [in-]action by a variety of actors so far. The methodology used collective and iterative mapping processes, using technical, organizational and geographical knowledge from a variety of governance, experts and practitioner networks in Lima. The main outcome is the social learning derived from bringing together different kinds of knowledge and integrating several dimensions through spatial representations. This has raised awareness, increased capacities for dealing with uncertainty and contributed to the approved metropolitan Climate Change Adaptation Strategy, but not implemented by the Lima Municipality yet. The main conclusions are two: 1) spatial planning is a quite political process (c.f. Flyvbjerg 1998), in which knowledge is contested or even when acknowledged, does not necessarily steer decision-making processes, either by local communities, authorities and private institutions. And 2) existing models linking knowledge construction to risk framing, risk tolerance and how these influence decision-making processes and actions to prevent disaster may ignore the issues of risk tolerance, through normalization and prioritization at their peril.